2000
DOI: 10.1680/adcr.2000.12.3.97
|View full text |Cite
|
Sign up to set email alerts
|

Development of large steelmaking slag blocks using a new carbonation process

Abstract: Porous slag blocks (1 m3) were produced by carbonation of steelmaking slag over a period of 12 days. The compressive strength and bulk density of the blocks were 18·4 ± 3·3 MPa and 2·4 g/cm3, respectively. To make a large block, the optimum amount of water and bulk density of the compact were 5·3–6·3 mass% and 2·30–2·37 g/cm3, respectively. The carbonation reaction occurred homogeneously in the blocks, and the amount of CO2 that reacted with the slag was approximately 6 mass% at all depths from the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…by (hydraulic) compaction; and (3) CO 2 curing in an autoclave (at elevated CO 2 pressure) or in a climate chamber (at low CO 2 pressure). In 1999 large porous blocks (1mx1mx1m) were made using only steelmaking slag and CO 2 [44]. The blocks were produced by moist carbonation in an airtight mold.…”
Section: Case 2: Carbonate Bonded Compactsmentioning
confidence: 99%
See 1 more Smart Citation
“…by (hydraulic) compaction; and (3) CO 2 curing in an autoclave (at elevated CO 2 pressure) or in a climate chamber (at low CO 2 pressure). In 1999 large porous blocks (1mx1mx1m) were made using only steelmaking slag and CO 2 [44]. The blocks were produced by moist carbonation in an airtight mold.…”
Section: Case 2: Carbonate Bonded Compactsmentioning
confidence: 99%
“…The compressive strength of the resulting blocks reached 18±3 MPa. The blocks were carbonated homogeneously and the CO 2 uptake was approximately 6 % [44]. The NKK corporation (presently JFE steel) started marketing these blocks under the registered trade nameMarine Blocks for constructing artificial reefs [52].…”
Section: Case 2: Carbonate Bonded Compactsmentioning
confidence: 99%
“…However, steel slag has shown the potential to replace cement as an alternative binder if carbonation activation is performed (Mahoutian and Shao 2016). Isoo et al (2000) reported that a 1 m 3 slag block reached a compressive strength of 18.4 MPa after 12 days of carbonation for seaweed bed application. Stainless steel slag compacts exposed to carbon dioxide for one hour achieved a compressive strength of 9 MPa and a carbon dioxide uptake of D r a f t 18% (Johnson et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…5% , but this kind of hydraulic steel slag stimulated amplification can be treated with a certain way [7]. In recent years, it has been widely used in the field of traditional building materials: production of steel slag cement, preparation of steel slag concrete, and backfilling and reinforcement of foundation [8,9]. According, to the research, the slurry can stimulate the potential activity of steel slag, and the slurry is also the ideal material for fixing CO2 and preparing slag products [10].…”
Section: Introductionmentioning
confidence: 99%